2015
DOI: 10.3109/1061186x.2015.1066794
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid induces NET cell growth arrest and enhances tumor suppression of the receptor-targeted peptide–drug conjugate via activating somatostatin receptor type II

Abstract: The combination of VPA and a SSTR2-targeting agent provides us a promising approach in treatment of carcinoid tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 42 publications
6
31
1
Order By: Relevance
“…Previous studies suggested effects on a transcriptional level via DNMT and HDAC inhibition (26,27) and on a translational level via HDAC inhibition (28). In the present study, we confirmed these findings and expanded the principle to the functional level in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies suggested effects on a transcriptional level via DNMT and HDAC inhibition (26,27) and on a translational level via HDAC inhibition (28). In the present study, we confirmed these findings and expanded the principle to the functional level in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies on HDAC inhibition of NET cells have shown activation of Notch1 signalling after VPA treatment. It was also proposed that Notch1 activation is a crucial step in VPA-induced growth inhibition of NET cells [30,31,32]. In the present study, however, pathway analysis identified Notch1 as a significantly affected upstream regulator in GOT1 cells only, while the magnitude of activation was low (Z score = 0.3).…”
Section: Resultscontrasting
confidence: 47%
“…However, at this time point, VPA induced upregulation of NOTCH2 expression in GOT1 and BON cells, suggesting activation of Notch family members. A recent study analysed the expression of Notch1 in BON cells over time and showed that Notch1 expression was upregulated only after chronic exposure to VPA [32]. That study also provided evidence that activation of Notch1 does not account for all the anti-tumour effects of VPA treatment.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…This effect was however only prominent at high doses, suggesting that observed effects might be due to off-target activity. HDAC inhibition has also previously been suggested as a treatment option for GEPNET patients (Baradari et al 2006, Sun et al 2016.…”
Section: :3mentioning
confidence: 99%